The Effect of a Combination of Coconut Dregs and Fermented Chicken Manure on Population, Weight and Length of Maggots (Hermetia illucens) - Akhirudien, Akhirudien; Mulyono, Ali Mursyid Wahyu; Sukaryani, Sri (Jurnal Biologi Tropis, 2024)
Maggot is an organism that originates from the eggs of the BSF fly (Black Soldier Fly) which is usually known as a rotting organism because of its habit of consuming organic materials. Maggots can be an alternative feed because they have a fairly high protein content and are suitable as fresh fish feed or as raw fish feed ingredients. The study aims to determine the effect of the proportion of the combination of coconut pulp and fermented chicken manure on the population, weight and length of maggot (Hermetia illucens). This research method used an experiment with 6 treatments, 5 replicates for each treatment. The treatments applied were T1: 100% coconut pulp, T2: 95% coconut pulp + 5% chicken manure, T3: 90% coconut pulp + 10% chicken manure, T4: 85% coconut pulp + 15% chicken manure, T5: 80% coconut pulp + 20% chicken manure, T6: 75% coconut pulp + 25% chicken manure. Maggot maintenance started from 0-14 days of age.  The observed paramameter of the population were weight and length of maggot (Hermetia illucens). This study used a Complete Random Design (RAL) with 5 replicates and the data was analyzed using Analysis of Variance (ANOVA). Based on the results of statistical analysis, the combination of coconut pulp and fermented chicken manure on the population, weight and length of manggot (Hermetia illucens) (P < 0.05). The results of the research on the combination of coconut pulp and fermented chicken manure with different combinations showed that there were some differences. T6 treatment was able to show the highest results in population, weight and length of maggot (Hermetia illucens).